PERLINDUNGAN HUKUM HAK CIPTA ATAS TARI TOPENG DAN SINTREN DI CIREBON - Andini, Artri (MIH FH UNSOED, 2015)
Mask dance and the folklore Sintren in Cirebon, this needs to be raised, given the many meanings and values contained therein. Therefore the legal instruments in use today need to be evaluated. Legal protection of folklore has unwittingly become a big problem and quaint because not any legislation in Indonesia who set about legal protection of intellectual property. The Research Type is normative-empirical research. The approximation methods are two kinds; first problem using a legislation conceptual and analytical approach and purposive sampling for the second problem. The data source consist of primary data and secondary data. The research on the legal protection of Topeng dance and Sintren at Cirebon is Preventive Legal Protection is a regulation made by central and local government related to folklore including copyright laws number 19 of 2002 especially arranged in section 10, local regulation of West Java Province Number 5 of 2012 about Intellectual Property Protection and both central and local government policies that related to folklore; Represive Legal Protection is a legal protection effort undertaken by the state in case there are claims of the other states upon Indonesia folklore.Keywords: Legal Protection, Copyright, Topeng dance and Sintren